Hepatitis C virus infection and the risk of cancer among elderly US adults: A registry‐based case‐control study. Issue 7 (24th January 2017) - Mahale, Parag; Torres, Harrys A.; Kramer, Jennifer R.; Hwang, Lu‐Yu; Li, Ruosha; Brown, Eric L.; Engels, Eric A.
Abstract : BACKGROUND: Hepatitis C virus (HCV) infection causes hepatocellular carcinoma (HCC) and subtypes of non‐Hodgkin lymphoma (NHL). Associations with other cancers are not established. The authors systematically assessed associations between HCV infection and cancers in the US elderly population. METHODS: This was a registry‐based case‐control study using Surveillance, Epidemiology, and End Results (SEER)‐Medicare data in US adults aged ≥66 years. Cases (n = 1, 623, 538) were patients who had first cancers identified in SEER registries (1993‐2011). Controls (n = 200, 000) were randomly selected, cancer‐free individuals who were frequency‐matched to cases on age, sex, race, and calendar year. Associations with HCV (documented by Medicare claims) were determined using logistic regression. RESULTS: HCV prevalence was higher in cases than in controls (0.7% vs 0.5%). HCV was positively associated with cancers of the liver (adjusted odds ratio [aOR] = 31.5; 95% confidence interval [CI], 29.0‐34.3), intrahepatic bile duct (aOR, 3.40; 95% CI, 2.52‐4.58), extrahepatic bile duct (aOR, 1.90; 95% CI, 1.41‐2.57), pancreas (aOR, 1.23; 95% CI, 1.09‐1.40), and anus (aOR, 1.97; 95% CI, 1.42‐2.73); nonmelanoma nonepithelial skin cancer (aOR, 1.53; 95% CI, 1.15‐2.04); myelodysplastic syndrome (aOR, 1.56; 95% CI, 1.33‐1.83); and diffuse large B‐cell lymphoma (aOR, 1.57; 95% CI, 1.34‐1.84). Specific skin cancers associated with HCV were Merkel cell carcinoma (aOR, 1.92; 95% CI, 1.30‐2.85) and appendageal skin cancers (aOR, 2.02; 95% CI, 1.29‐3.16). Inverse associations were observed with uterine cancer (aOR, 0.64; 95% CI, 0.51‐0.80) and prostate cancer (aOR, 0.73; 95% CI, 0.66‐0.82). Associations were maintained in sensitivity analyses conducted among individuals without documented alcohol abuse, cirrhosis, or hepatitis B or human immunodeficiency virus infections and after adjustment for socioeconomic status. Associations of HCV with other cancers were not observed. CONCLUSIONS: HCV is associated with increased risk of cancers other than HCC in the US elderly population, notably bile duct cancers and diffuse large B‐cell lymphoma. These results support a possible etiologic role for HCV in an expanded group of cancers. Cancer 2017;123:1202–1211. © 2016 American Cancer Society . Abstract : Chronic hepatitis C virus infection is a cause of hepatocellular carcinoma, but its associations with other cancers are uncertain. Nationally representative data from an elderly US population in the Surveillance, Epidemiology, and End Results‐Medicare–linked database indicates that hepatitis C virus is associated with increased risks of intrahepatic and extrahepatic cholangiocarcinoma and diffuse large B‐cell lymphoma. See also pages 1086‐8.